Improving English Language through Listening Podcast - Aulia, Dinda Sabda; Santoso, Didik (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The use of podcasts is very helpful for creating activities in the classroom and students seemed to be very motivated and interested in listening and to listen and practice speaking. The Students were able to take specific information from the podcasts and work in groups to use the information. Podcasts present a variety of interesting topics that can broaden that can broaden students' horizons. By using instructional technology technology, such as podcasts, teachers can also and develop their skills in using the technology. with the technology. This is evident with their English intonation production, students tend to raise the pitch at the end of a declarative sentence. declarative sentences, which automatically changes the mood of the sentence into an integrative sentences. In addition, this study also shows that English learners have inadequate knowledge of suprasegmental features in English, especially intonation. This This shows that teaching English, especially pronunciation, can be very difficult because students perceive intonation as a students' perception of intonation in relation to native speakers' use of English intonation. By using podcasts, in addition to practicing English, students can also be entertained and increase their enthusiasm for learning. Therefore, podcasts can be considered as an important medium in English language teaching.